Composting | KC - Rostek, Andrew (Kansas State University, 2016)
Kansas City is currently under achieving in its capacity of divert recyclable and compostable solid waste from city landfills. The city recycling system provides free access to single family residents, but it does not provide access to high density residential and commercial land uses commonly found Downtown. To solve this dilemma, KCDC has studied the current solid waste systems in the city, and developed its [re]considered proposal through a MARC Solid Waste Management District grant to improve Kansas City waste diversion. This is achieved through a system of links, clusters and nodes which will help to promote and facilitate greater recycling (KCDC 2015 Fall Studio 2015) Compost | KC seeks to answer if the organic nodes as proposed in can effectively compost residential organic waste in down town Kansas City. As part of this system, the organic node at 12th and Holmes functionally demonstrates the potential feasibility and benefits of residential compost of organic solid waste. Through the site design, the proposed organic node creates an integrated system of residential organic waste collection, processing and utilization. Collected form a 15 minute radius the waste is processed into a rich organic compost that is used in various ways to improve soil quality for stormwater management, carbon sequestration, and increased biomass production in and around the site. To compost the organic waste, the site contains a series of in-vessel composting drums, agitated compost piles connected to greenhouses, and an external maturing pile visibly demonstrating and educating the public composting benefits. Managed through a local non-profit organization, compost is used to grow a variety of produce and nursery stock sold to help fund the site management. Organic waste is brought to the site by organized collection with apartment complexes and free public drop-off points. By incentivizing access, ease and appeal of composting in Kansas City for residences, the organic node at 12th and Holmes achieves the goals of both the site design and [re] considered proposals. By meeting those goals, the organic node helps to increase organic waste diversion and increase education and awareness about the benefits of composting in downtown Kansas City.
Keywords: Landscape Architecture; Compost; Urban Agriculture; Organic Waste; Recycling; Urban Design